Narratives and Their Impact on Students’ Information Seeking and Critical Online Reasoning in Higher Education Economics and Medicine - Banerjee, Mita; Zlatkin-Troitschanskaia, Olga; Roeper, Jochen (Frontiers in Education, 2020)
The digital and information age has fundamentally transformed the way in which students learn and the study material they have at their disposal, especially in higher education. Students need to possess a number of higher-order cognitive and metacognitive skills, including effective information processing and critical reasoning to be able to navigate the Internet and use online sources, even those found outside of academically curated domains and in the depths of the Internet, and to solve (domain-specific) problems. Linking qualitative and quantitative research and connecting the humanities to empirical educational science studies, this article investigates the role of narratives and their impact on university students’ information seeking and their critical online reasoning (COR). This study focuses on the link between students’ online navigation skills, information seeking behavior and critical reasoning with regard to the specific domains: economics and medicine. For the empirical analysis in this article, we draw on a study that assesses the COR skills of undergraduate students of economics and medicine at two German universities. To measure COR skills, we used five tasks from the computer-based assessment “Critical Online Reasoning Assessment” (CORA), which assesses students’ skills in critically evaluating online sources and reasoning using evidence on contentious issues. The conceptual framework of this study is based on an existing methodology – narrative economics and medicine – and discusses its instructional potential and how it can be used to develop a new tool of “wise interventions” to enhance students’ COR in higher education. Based on qualitative content analyses of the students’ written responses, i.e., short essays, three distinct patterns of information seeking behavior among students have been identified. These three patterns – “Unambiguous Fact-Checking,” “Perspective-Taking Without Fact-Checking,” and “Web Credibility-Evaluating” – differ substantially in their potential connection to underlying narratives of information used by students to solve the CORA tasks. This analysis suggests that training university students in narrative analysis can strongly contribute to enhancing their critical online reasoning.